The Totally True Story of Me! - Tibo, Gilles; Bisaillon, Josee (USA, 2008)
A young girl shares many things, including thoughts on becoming a big sister, freedom, joy, death, peace, and hope, through secrets, lists, poems, and inventions recorded in her diary...
Keywords: Diaries - Emotion & Feelings; Education; Juvenile Fiction; Schools